Monarchs and hydrarchs - Cooijmans, Christian, author.
1 online resource.
Keywords: "Monarchs and Hydrarchs approaches the available interdisciplinary data on a cumulative and conceptual level, allowing overall spatiotemporal patterns of Viking activity to be detected and defined. Despite decades of scholarly scrutiny, the politico-economic exploits of Vikings in and around the Frankish realm (c. 750-940 CE) remain - to a considerable extent - obscured by the constraints of a fragmentary and biased corpus of (near-)contemporary evidence, conveying the impression that these movements were capricious, haphazard, and gratuitous in character. Set against a backdrop of continuous commerce and knowledge exchange, this overarching survey demonstrates the existence of a relatively uniform, sequential framework of wealth extraction, encampment, and political engagement, within which Scandinavian fleets operated as adaptable, ambulant polities - or 'hydrarchies'. By delineating and visualising this framework, a four-phased conceptual development model of hydrarchic conduct and consequence is established, whose validity is substantiated by its application to a number of distinct regional case studies. The parameters of this abstract model affirm that Scandinavian movements across Francia were the result of prudent and expedient decision-making processes, contingent on exchanged intelligence, cumulative experience, and the ongoing individual and collective need for socioeconomic subsistence and enrichment. It will appeal to researchers wishing to understand Viking interactions with the Franks as well as more generally to students and academics in Early Medieval and Viking Studies"--